2023
DOI: 10.3389/fpubh.2023.1277378
|View full text |Cite
|
Sign up to set email alerts
|

E-scooter attitudes and risk-taking behaviours: an international systematic literature review and survey responses in the West Midlands, United Kingdom

Nathalie Burt,
Zubair Ahmed

Abstract: IntroductionMicromobility initiatives, including electric scooters (e-scooters), are part of the United Kingdom government’s sustainability drive. Since summer 2020, multiple trials have been conducted across the United Kingdom. Safety concerns have been raised around e-scooters joining other vehicles on United Kingdom roads, alongside the numerous private e-scooters illegally ridden on public land. Although literature has been published abroad on perceptions, risk-taking behaviours and attitudes surrounding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…2 Due to similar use and theoretical speed, some studies compare ESs and bicycles. 3-5 Nevertheless, compared to cycling, the risk of ES-related injuries has been defined as 3.8 times higher. 3,4 Electric scooters are more like electric mopeds, despite the latter requiring a driving license and helmet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Due to similar use and theoretical speed, some studies compare ESs and bicycles. 3-5 Nevertheless, compared to cycling, the risk of ES-related injuries has been defined as 3.8 times higher. 3,4 Electric scooters are more like electric mopeds, despite the latter requiring a driving license and helmet.…”
Section: Introductionmentioning
confidence: 99%
“…Available studies describe heterogeneous data, as shown in previous reviews. 2,5 In 2022 Singh et al focused on demographics and injury types with large eligibility criteria, requiring an updated and differently structured analysis. Similarly, Toofany et al described the injury patterns to a lesser extent due to a different methodology; furthermore, they included patients younger than 18 years and, finally, followed a less rigorous paper selection.…”
Section: Introductionmentioning
confidence: 99%